International Public Sector Accounting Standards and Economic Growth: An International Study of IPSAS Adoption and Experience - Fatma Ben Slama (Journal of Accounting and Management Information Systems (JAMIS), 2024)
Research Question- What impact has the implementation of International Public Sector Accounting Standards (IPSAS) had on gross domestic product (GDP) growth in countries that have fully adopted these standards? Motivation- The results of prior research are inconclusive, and more research is needed to understand the potential impact of IPSAS on the economic growth of adopting countries. Despite the abundance of empirical studies on the determinants of economic growth, much remains to be done to achieve a conclusive understanding of this complex issue, as noted by Owusu et al. (2017). The existing literature is mainly concerned with standard economic factors and does not consider the critical role played by the national accounting framework, in particular the underlying accounting rules. As a result, research on economic growth has tended to focus on global and macroeconomic trade issues rather than accounting issues. These criticisms highlight the need for more rigorous studies to assess the impact of the adoption of IPSAS especially in different socio-economic and political contexts. Idea- This study tests the impact of IPSAS adoption and experience on the economic growth rate, controlling for variables that may influence economic development, such as foreign direct investment (FDI), public investment (INV), trade openness (OPEN), capital expenditure (EXPEND) and COVID pandemic (COV19). Data- The data was collected from 18 countries that were engaged in the process of international adoption between the years 2009 and 2022. Tools- Multivariate analysis on panel data was applied. Findings- Our results show that adopting IPSAS and the country's experience with the new standards set, positively and significantly affect economic growth. Furthermore, public investment and trade openness are significant positive determinants of economic growth. On the other hand, the COVID 19 pandemic and public expenditure negatively affect GDP growth. Contribution- The paper results could be of practical interest to governments in their decision to move to IPSAS and to standard setters and international institutions, which encourage countries to reform their public accounting systems through coercive isomorphism. Adopting IPSAS can also have macroeconomic benefits through a better reputation with international donors.
Keywords: H83; O47; 650; IPSAS; IPSAS experience; Public accounting- Gross Domestic Product (GDP) growth; international study; public investment; trade openness